Malcolm X : Pengaruh dan Konflik Internal dalam Gerakan Nation of Islam (NOI) di Amerika Serikat (1952-1965) - Sidik Fauji (Aqlam: Journal of Islam and Plurality, 2021)
Abstract: This research aim to analyze the influence of Malcom X in the movement of NOI, and how it ignite internal conflict within this organization. The analyze focused on library research by using history research method. History research method requires certain procedures for instance heuristic, verification, interpretation, and historiography. As a result, there are three significant factors that triggered the violence againt Malcolm X performed by NOI perpetrators. The first factor was assumed on the popularity of Malcolm X whom gained more attention than Elijah Muhammad did. The consequences of Malcolm X’s fame initiated the jelaousy toward him. As a result there was rumour produced by Elijah Muhammad followers on the agenda of coup d’etat  against the leadership of the legal chief of NOI. The next cause of the internal conflict within NOI was the scandal of Elijah Muhammad with his female secretary. The last factor was the Malcolm X opinion on mass media toward the homicide of President Kennedy. Keywords : Influence, Internal Conflict, Malcolm X, NOI. Abstrak: Penelitian ini dilaksanakan dengan tujuan untuk menjelaskan pengaruh Malcolm X dan konflik internal dalam gerakan NOI. Penelitian ini dipusatkan pada kajian pustaka dengan menggunakan metode penelitian sejarah. Langkah yang dilakukan peneliti yaitu heuristik, kritik sumber, interpretasi dan historiografi. Hasil dari penelitian ini adalah setidaknya ada tiga faktor utama yang menyebabkan konflik Malcolm X dari NOI. Pertama, Malcolm X lebih terkenal dan menjadi tokoh besar dalam gerakan NOI daripada Elijah Muhammad. Ketenarannya merangsang rasa iri dan rumor bahwa dia akan mengambil alih gerakan serta dia ingin lebih berhasil dari Elijah Muhammad. Kedua, kehidupan pribadi Elijah Muhammad yang terguncang oleh skandal perempuan. Ketiga adalah komentar Malcolm X pada pembunuhan Presiden Kennedy.Kata Kunci : Pengaruh, Konflik Internal, Malcolm X, NOI